Plant physiology in South America: diagnostics and perspectives - Habermann, Gustavo [UNESP] (Springer Nature, 2015)
This is a short text about a lecture I gave during the XV Congress of the Argentinian Society of Plant Physiology, in Mar del Plata, in September 2014. In this Opinion, I show some scientometrics of science and plant science that have been performed in South America. Plant Physiology, in my opinion, is loosing the battle to the “omics” when it comes to dealing with challenges related to plant science. Plant physiology was born from a systemic understanding of the plant functioning. Therefore, actually, we should work together with other disciplines in order to propose interesting ideas to enhance rates of crop yields increase. Otherwise, we will have to accept more biodiversity destruction to expand lands for agriculture, food insecurity and food inflation.
Keywords: Argentinian Society of Plant Physiology; Brazilian Society of Plant Physiology; Plant science; Scientiometrics